Penerapan Metode Project Based Learning dikombinasikan Flipped Classroom Terhadap Kemampuan Berpikir Kritis - Dona Fitriawan; Endar Sulistyowati; Nurfadilah Siregar (LPPM Universitas Advent Indonesia, 2024)
Education must keep up and adapt to continue to meet global challenges and the needs of individuals and society. This includes a more flexible approach, integrating technology, and focusing on skill development to suit the modern world. Therefore, educational practitioners must be able to meet these needs so that the teaching and learning process can always go hand in hand. This study used a pseudo-experimental design with a population of all 5th semester students and hypothesis testing using the t test. The test results with a two-sample t test obtained the results of Thitung 4.71 and Ttabel 3.21, this shows that at the sig level of 0.05, the value of Thitung > Ttabel. This means that H0 is rejected, and H1 so it can be concluded that there is an effect of applying the PjBL model combined with FC on students' critical thinking skills.